Strategies for Designing Titles and Problem Formulations as a Foundation for Quality Educational Research - Soni Sultansah; Tedi Priatna; Bayu Bambang Nurfauji; Dea Hilyatul Aulia; Nur Sholehah (Kasyafa: Jurnal Pendidikan Agama Islam, 2026)
This study examines the essential role of research title construction and problem formulation in educational research. A research title serves as a concise conceptual indicator of the study’s scope, variables, and context, while the formulation of a research problem provides the intellectual foundation that guides objectives, methodological choices, and data analysis. Despite their importance, many novice researchers continue to struggle in identifying researchable problems and aligning them with coherent titles. Using a descriptive qualitative approach supported by literature analysis, this study finds that effective titles must be clear, relevant, and reflective of meaningful educational issues. Likewise, a well-formulated problem must address a genuine conceptual or empirical gap and be feasible for investigation. Findings demonstrate that clarity in problem formulation strongly correlates with methodological coherence and the overall quality of research outcomes. Conversely, vague problems often lead to weak analytical conclusions. This study underscores the need for stronger methodological literacy among educators and students.